Efficiency of concentrated bone marrow aspirate combination with temporary fixation of the scaphoid-trapezius-trapezoidal joint in Kienbeck’s disease - Tymochenko, м; Gajovich, Igor; Аbbasov, Sаmir; Lysak, Аndrij (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Method of concentrated bone marrow aspirate (BMAC) injection into aseptic bone necrosis of different localizations are described in the literature, however, without demonstrating structural and functional results for Kienbeck’s disease. Objective. To establish functional and radiological changes at injection of concentrated bone marrow aspirate into lunate bone in combination with scaphoid-trapezoid-trapezius joint temporary fixation in patients with idiopathic lunate bone necrosis. Methods. The procedure was performed in 11 patients. Age 18–46 years (28,9 ± 9,5) 6 women, 5 males. Kienbeck's disease stage II — 4 patients, IIIa — in 2, IIIb in 5 patients. Bone marrow aspirate concentration from the iliac bone was obtained using Arthrex-Angel technique, injection of 2–3 ml of the concentrate with intraosseous needle under X-ray control into the focus of aseptic necrosis of the lunate bone, STT-fixation of the wrist joint in the position of rotational correction of the scaphoid. Immobilization followed for 2 months, than removal of the K-wires and rehabilitation. X-ray, CT control and DASH testing before the procedure and in a year. Results. Five patients (45 %) had a distinct positive clinical and radiological dynamics, definite positive changes on CT (pathological fracture consolidation, lunate bone remodeling), as well as DASH scale improvement, maintenance of wrist joint radiometric parameters and an increase in strength and range of motions in the wrist. Four patients had no significant dynamics, and in two patients there was a distinct decline in function, advance lunate bone destruction, and an increased wrist joint instability. Conclusions. The technique requires advance revision of the conditions under which it demonstrates its effectiveness. Today it can be recommended in addition to other surgical procedures (shortening of the radius, STT arthrodesis), which have more predicted effectiveness.